A Method for Assessing the Flexibility of Buildings to Dismantle and Reuse Their Structural Elements - Strzelecki, Mirosław; Markuszewska, Kornelia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to develop and verify a method for assessing building structural solutions in terms of their susceptibility to dismantling and reuse, referred to as circular flexibility. The novelty of the approach lies in its focus on load-bearing elements and the application of a simple Weighted Sum Model (WSM) that enables the comparison of structural solutions already at the design stage.
Keywords: circular architecture; reuse; building structures; dismantling; circular economy (CE)